Udział stowarzyszeń zwykłych w postępowaniu sądowoadministracyjnym w sprawach z zakresu ochrony środowiska – analiza rozbieżności w orzecznictwie - Korzeniowski, Piotr (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
Participation of unincorporated associations in court and administrative proceedings is a tool of public participation which is a part of basic principles of performance of a democratic country and a civil society. By means of abiding by those principles administrative bodies and courts respect the rule of law and it becomes a standard. The rule of public participation can be as well treated as a part of the basic civil rights stipulated in the Constitution. By respecting the right of unincorporated associations to participate in court and administrative proceedings in environmental protection-related cases the goals and functions of environmental protection law can be accomplished.